2020
DOI: 10.1021/acs.joc.0c01093
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of 2,4-Diacyl Thiophenes from α-Oxo Ketene Dithioacetals and Propargylic Alcohols

Abstract: Although thiophenes having various functionalities are the basic structural units in numerous bioactive compounds and optoelectronic materials, synthetic routes to acylated thiophenes from aliphatic sulfur-containing starting materials are still rare. In particular, there have been no reports concerning the straightforward synthesis of 2,4-diacylthiophenes from alkynes. Herein, we describe a highly efficient and metal-free three-step one-pot synthetic approach to tetrasubstituted 2,4-diacylthiophenes from prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…68−70 In addition, thieno[2,3-b]thiophene 11 was achieved when 3a was treated with ethyl diazoacetate in the presence of Cu(OTf) 2 (Scheme 6c). 14 In conclusion, a visible-light-induced catalytic [3+2] oxidative cyclization of alkynes with ketene dithioacetals under very mild metal-free conditions without using a base or an oxidant was developed. We found that the easily available ketene dithioacetals can be activated to form a thiavinyl 1,3dipole equivalent.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…68−70 In addition, thieno[2,3-b]thiophene 11 was achieved when 3a was treated with ethyl diazoacetate in the presence of Cu(OTf) 2 (Scheme 6c). 14 In conclusion, a visible-light-induced catalytic [3+2] oxidative cyclization of alkynes with ketene dithioacetals under very mild metal-free conditions without using a base or an oxidant was developed. We found that the easily available ketene dithioacetals can be activated to form a thiavinyl 1,3dipole equivalent.…”
mentioning
confidence: 99%
“…Heterocyclizations are powerful tools for the synthesis of five-membered heterocycles that are often found in natural products , and synthetic pharmaceuticals and widely used in material science and organic synthesis. Recent studies revealed that oxidative heterocyclizations could evoke novel and useful catalytic transformations, which otherwise are difficult to achieve. For example, the cyclization of ketene dithioacetals, a kind of electron-rich olefin, under electrochemical conditions afforded the cyclic amino acid derivatives (Scheme a, X = NH) .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Selectfluor is not only a powerful fluorination reagent commercially available but also recognized as an exceptionally stable, nonvolatile, nonhygroscopic, and mild oxidant, which has been extensively used for efficient construction and site-selective C–H direct functionalization of heterocyclic molecules. , On the other hand, ketene dithioacetals, as versatile building blocks, permit the rapid assembly of structurally diverse carbo-/heterocyclic architectures through different cycloaddition or annulative coupling reaction processes . Following our continuous interest in selectively developing a new cyclic backbone based on them, we here described a metal-free Selectfluor-mediated direct synthesis of highly functionalized isothiazolones from easily synthesized α-carbamoyl ketene dithioacetals involving intramolecular N–S bond formation.…”
Section: Introductionmentioning
confidence: 99%